Diffusivity, permeability and solubility of H2, Ar, N2, and CO2 in poly(tetrafluoroethylene) between room temperature and 180 °C. (February 2016) - Sebők, Béla; Schülke, Mark; Réti, Ferenc; Kiss, Gábor
Abstract: The transport parameters of hydrogen, argon, nitrogen and carbon dioxide through a 0.1 mm thick poly(tetrafluoroethylene) (PTFE) membrane are investigated. The pre-exponential factors and activation energies for the diffusivity and permeability as well as the heat of solutions for these gases are reported based on a considerable number of experiments conducted between room temperature and 180 °C.